Analisis Jumlah Sel Eritrosit Darah Tikus Putih Jantan (Rattus norvegicus) Strain Wistar Sebelum dan Setelah Perlakuan Ekstrak Buah Merah (Pandanus conoideus) - Agnes S. Rahayu; Elieser Elieser (Jurusan Biologi FMIPA Universitas Cenderawasih, 2018)
The aim of this research was to measure the differences amount of erythrocytes in the blood of the rat (Rattus norvegicus) strain wistar before and after been given of the extract of the red fruid (Pandanus conoideus). This was a pre experiment with The One Group Pre Test – Post Test only design, the extract of red fruit (P. conoideus) was the independent variable and the dependent variable was the amount erythrocyte in rat blood. After the acclimatisation program in 7 days, the blood of this 20 rats were taken to measure the erythrocytes. For the next 7 days, all of the rats were given the extract of red fruit per oral by the sonde 5m/bb. The blood were taken again to measure the erythrocytes again, in the day after the last given of the extract of red fruit. The data were tabulated for normality test with Shapiro-wilk (SPSS v.24), homogeneity test, Levene test, and followed by Paired T-Test. The results were show that the mean of the erythrocyte before given the extract of red fruit was 5.54 x 106/mm3 and after that was 7.65 x 106/mm3. Key words: R. novergicus, P. conoideus, erythrocyte.